Community Participatory Approaches for Creative Tourism Development: Selected Cases in Thailand - Songserm, Nonthawan; Batra , Adarsh (Dusit Thani College Journal, 2020)
In Thailand, culturally-related tourism activities are not new to tourism industry, but it is evidently still left unrecognized and untended by the stakeholders on how to realize and add the creative elements to the existing tourism assets. This study concentrates on exploring positive mechanisms of community participation approaches in developing creative tourism products for achieving the best of what might be, instead of continuing to emphasize on the community’s problems. The proposed approaches are built upon Appreciative Participatory Planning and Action (APPA) techniques, which allow communities to identify their specific strengths and successes as a means to creatively and positively open up possibilities in the design of tourist assets. Based on a proposed 8-D cycle approach of Define, Discovery, Dream, Direction, Design, Delivery, Dance and Dialogue, this Appreciative Inquiry (AI) model provides a framework for community participation development planning to give community members a chance to have control over their own development process and make decisions that affect their livelihoods. Apparently, evidences from the selected case examples show that creative tourism development planning needs to be designed in an innovative setting with the right mechanism to drive group dynamics. In order for creative tourists to feel a part of the community, the residents have to understand the integration between the supply and demand sides, being proud of what they have, and at the same time must be willingly ready to create staged authenticity activities. Lesson learned from the application of the proposed model will be provided.